(untitled) (Journal of Chemical Engineering, 2014)
Electricity generation from the biodegradable organic substrate can be accompanied by wastewater treatment, which reduces the cost of industrial effluent treatment. In this study, effluent of local food-processing industries was treated in Membrane-Less Microbial Fuel Cell (ML-MFC) for electricity generation. Several investigations were conducted to enhance the current and voltage generation of MFC in different operating conditions, such as direct industrial effluent, adding drainage sludge concentration, aeration in cathode compartment, increasing the electrode area. In addition, COD removing capability of the ML-MFC was also studied. The study documented a maximum power density of 7.11874mW/m2 with the current density of 97.34mA/m2. COD removal was observed 47% to 74% in all experiments. DOI: http://dx.doi.org/10.3329/jce.v27i2.17803 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 2, December 2012: 55-59